Peran Kepala Madrasah Aliyah Negeri 1 Jember Dalam Membangun School Branding - Syaihoni, Ach Lutfi; Ummah, Nur Ittihadatul (Rausyan Fikri Journal of Islamic Studies, 2023)
The Madrasah Head has three important roles in building school branding, namely, the role of the Madrasah Head as a manager, the role of the Madrasah Head as a leader, and the role of the Madrasah Head as an entrepreneur. School branding is a word that comes from the word brand which means brand. In the educational environment, apart from improving the quality of education, school branding is also something that must be done by any Madrasah. School branding is the image of the Madrasah towards the community. Apart from having a positive impact on the Madrasah, school branding also includes communication between the Madrasah and the general public to attract the interest of students. The aim of this research is to describe the role of the Head of Madrasah Aliyah Negeri 1 Jember as a manager, leader, entrepreneur in building school branding. This research uses a qualitative approach with descriptive research, data collection techniques using observation, interviews and documentation. Data analysis using interactive model qualitative analysis. Data validity uses technical triagulation and source triagulation. The results of this research show, first, the role of the Madrasah Head as manager in building school branding is carried out in a structured manner, starting from; planning, organizing, implementing, and supervising. Second, the role of the Madrasah Head as a leader in building school branding, namely by providing direction, building communication, being brave in decision making, and motivating. Third, the role of the Madrasah Head as an entrepreneur in building school branding, namely through innovation, being proactive in taking firm action, daring to take risks, aggressively competing, and autonomy.Kepala Madrasah memiliki tiga peran penting dalam membangun school branding yaitu, peran Kepala Madrasah sebagai manager, peran Kepala Madrasah sebagai leader, dan peran Kepala Madrasah sebagai enterpreneur. School branding merupakan sebuah kata yang berasal dari kata brand yang berarti merk. Dalam lingkungan pendidikan selain meningkatka mutu pendidikan, School branding juga merupakan hal yang harus dilakukan oleh Madrasah manapun. School branding adalah pencitraan Madrasah terhadap masyarakat, selain berdapak positif terhadap Madrasah, school branding juga mencakup komunikasi Madrasah dengan masyarakat umum untuk menarik daya minat peserta didik. Tujuan dari penelitian ini adalah untuk mendeskripsikan Peran Kepala Madrasah Aliyah Negeri 1 Jember sebagai manager, leader, enterpreneur dalam membangun school branding. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deksriptif, teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Analisis data dengan analisis kualitatif model interaktif. Keabsahan data menggunakan triagulasi teknik dan triagulasi sumber. Hasil penelitian ini menunjukkan, pertama, Peran Kepala Madrasah sebagai manager dalam membangun school branding dilakukan secara terstruktur yakni dimulai dari; perencanaan, pengorganisasian, pelaksanaan, dan pengawasan. Kedua, Peran Kepala Madrasah sebagai leader dalam membangun school branding yakni dengan memberikan pengarahan, membangun komunikasi, berani dalam pengambilan keputusan, dan motoivasi. Ketiga, Peran Kepala Madrasah sebagai enterpreneur dalam membangun school branding yakni melalui inovasi, proaktif dalam mengambil tindakan tegas, berani mengambil resiko, agresif berkopetisi, dan otonomi.